2020
DOI: 10.3390/ph13060126
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Co-Delivery of Timolol and Brimonidine from a Self-Assembling Peptide Hydrogel for the Treatment of Glaucoma: In Vitro and Ex Vivo Evaluation

Abstract: Effective pharmacotherapy during glaucoma treatment depends on interventions that reduce intraocular pressure (IOP) and retain the IOP lowering effect for sufficient time so as to reduce dosing frequency and enhance patient adherence. Combination anti-glaucoma therapy and dosage forms that increase precorneal residence time could therefore constitute a promising therapeutic intervention. The in-situ gel forming self-assembling peptide ac-(RADA)4-CONH2 was evaluated as carrier for the ocular co-delivery of timo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Specifically, given its ability to be degraded by trypsin, RAD16-I would be an excellent delivery platform for drug release into the small intestine. Moreover, RAD16-I has been used and demonstrated to be suitable as a carrier for drug encapsulation and controlled release kinetics [34,43,45,46] from the hydrogel by adjusting the peptide concentration and chemistry [53]. Finally, our results indicate that the self-assembling peptide RAD16-I can be digested into shorter peptide sequences and, subsequently, degraded into amino acids, which are a group of naturally biodegradable molecules.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Specifically, given its ability to be degraded by trypsin, RAD16-I would be an excellent delivery platform for drug release into the small intestine. Moreover, RAD16-I has been used and demonstrated to be suitable as a carrier for drug encapsulation and controlled release kinetics [34,43,45,46] from the hydrogel by adjusting the peptide concentration and chemistry [53]. Finally, our results indicate that the self-assembling peptide RAD16-I can be digested into shorter peptide sequences and, subsequently, degraded into amino acids, which are a group of naturally biodegradable molecules.…”
Section: Discussionmentioning
confidence: 76%
“…In this paper, some physicochemical features of the synthetic self-assembling peptide RAD16-I have been studied. This peptide is currently commercialized under the name of PuraMatrix TM and is being used as a scaffold in many biomedical applications and studies such as in the development of in vitro cancer models [27,39,40], in different tissue engineering scenarios [29,30,41,42] and it has also been tested as a platform for drug delivery [43][44][45][46]. Thus, in addition to performing all the necessary experiments to characterize the biological systems obtained for each different application, it is also essential to control and study all the properties regarding the biodegradability of the scaffold, which, to date, has not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Other polymer-based hydrogels evaluated for ophthalmic administration are stimulus-responsive gel [ 100 , 101 , 102 , 103 , 104 ]. These delivery strategies have been investigated for several ophthalmic drugs commonly used in the treatment of glaucoma, such as TM, brimonidine tartrate (BT), pilocarpine, and latanoprost, or combinations with each other [ 105 , 106 , 107 , 108 ] ( Table 2 ).…”
Section: Drug Deliverymentioning
confidence: 99%
“…The studies showed an extended-release of TM for up to 80 h [ 124 ]. An in situ gel forming self-assembling peptide, ac-(RADA) 4 -CONH 2 , was evaluated as a carrier for the ocular co-delivery of TM and BT by Taka et al [ 105 ]. A complete release of both drugs was obtained within eight hours.…”
Section: Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation